Treatment adherence in South African primary healthcare - A. Kagee (South African Family Practice)
Patient non-adherence to medical treatment regimens is a pressing problem in South African primary health care. The absence of a cogent research base in the South African context has meant that solutions to the problem of non-adherence continue to elude clinicians. This paper offers an understanding of patient non-adherence from the perspective of behavioural science. It focuses on the way in which adherence is conceptualised and assessed, and examines the social, economic and psychological factors associated with patient behaviour. Psychological issues that are highlighted as affecting adherence include health locus of control, self-efficacy, psychological morbidity, health literacy and quality of life. Commonly used intervention strategies to enhance treatment adherence are examined and health workers are alerted to the contributions of behavioural science in understanding this aspect of patient behaviour.